Thermodynamic and experimental explorations of CO2 methanation over highly active metal-free fibrous silica-beta zeolite (FS@SiO2-BEA) of innovative morphology. (16th January 2021) - Hussain, I.; Jalil, A.A.; Izan, S.M.; Azami, M.S.; Kidam, K.; Ainirazali, N.; Ripin, A.
Graphical abstract: Highlights: Thermodynamic and experimental study of CO2 methanation for substitute natural gas. CO2 /H2 ratio was an influential parameter to boost the CO2 methanation activity. Synthesis of a fibrous silica beta zeolite (FS@SiO2 -BEA) through microemulsion. High catalytic activity obtained at T = 500 °C, CO2 /H2 = 1:5, and P = 1 atm. Experimental results were consistent with thermodynamic observations. Abstract: CO2 methanation is a novel way for climate change mitigation by converting CO2 into substitute natural gas. In this study, a highly active fibrous silica-beta zeolite (FS@SiO2 -BEA) catalyst was prepared for CO2 methanation by a microemulsion process, and examined by N2 adsorption–desorption, field emission scanning electron microscope (FESEM), transmission electron microscopy (TEM), and electron spin resonance (ESR) spectroscopy techniques. It was found that the FS@SiO2 -BEA catalyst possessed a fibrous silica morphology, leading to high surface area (609 m 2 /g), oxygen vacancies, and basicity. A thermodynamic study was also carried out using Gibbs free energy minimization method, and it was found that low temperatures (25–350 °C) and high H2 : CO2 ≥ 4 ratios have enhanced the CO2 methanation activity. The prepared FS@SiO2 -BEA catalyst exhibited high CO2 conversion (65%), and CH4 selectivity (61%) with a space–time yield of 3.30 g gcat −1 h −1 . The obtained experimental results highly followed the thermodynamic calculations.